Two novel heterozygote mutations of ATM in a Chinese family with dystonia-dominant ataxia telangiectasia and literature review - Zhi-Jun Liu; Ya-Ling Wang; Yan Xu (Frontiers in Pediatrics, 2023)
BackgroundAtaxia-telangiectasia (A-T) is an autosomal recessive disorder with high clinical heterogeneity. A-T may present in complicated variable forms, including classic A-T and milder form of AT. Contrary to the classic A-T, the milder form does not present the cardinal features of A-T such as ataxia and telangiectasia. A few ATM mutations have been reported in variant A-T cases manifesting isolated generalized or segmental dystonia without any signs of classical A-T.MethodsAn A-T pedigree with predominant dystonia was collected. Genetic testing was performed by targeted panel of genes involved in movement disorders. The candidate variants were further confirmed by Sanger sequencing. We then reviewed previously published literatures of genetically confirmed A-T cases with predominant dystonia and summarized the clinical characteristics of dystonia-dominant A-T.ResultsTwo novel ATM mutations, p.I2683T and p.S2860P, were identified in the family. The proband presented isolated segmental dystonia without any signs of ataxia and telangiectasias. We reviewed the literatures and found that the patients with dystonia-dominant A-T tend to have a later-onset and slower progression of the disease.ConclusionTo our knowledge, this is the first report of A-T patient with predominant dystonia in China. Dystonia may appear as one of the predominant manifestations or initial symptom of A-T. Early ATM genetic testing should be considered for those patients with predominant dystonia, despite without accompanying ataxia or telangiectasia.